Characterization of the Antifungal Activity Against Botrytis Cinerea of Sclareol and 13-Epi-Sclareol, Two Labdane-Type Diterpenoids - Cotoras-Tadic, M; Mendoza-Espinola, L; Mendoza-Espinola, L (Sociedad Chilena de Quimica, 2015)
The antifungal activity of Sclareol and 13-epi-Sclareol, two labdane-type diterpenoids, on mycelial growth of the phytopathogenic fungus Botrytis cinerea was evaluated. Diterpenoid fungitoxicity was assessed using the radial growth test method. Both diterpenoids inhibited the mycelial growth of B. cinerea in solid medium; however the inhibitory activity of Sclareol was slightly higher than 13-epi-Sclareol with IC50 value of 237.6 μg/mL and 268.8 μg/mL, respectively. On the other hand, both labdane-type diterpenoids did not alter the plasmatic membrane integrity; however the oxygen consumption of B. cinerea germinating conidia was affected. The evidence suggests that action mechanism of these molecules would be related to the uncoupling of mitochondrial oxidative phosphorylation. Finally, biotransformation of Sclareol by B. cinerea was analysed and the main biotransformed metabolite was identified as 3β-hydroxysclareol.